2018
DOI: 10.1080/17429145.2018.1491648
|View full text |Cite
|
Sign up to set email alerts
|

Penconazole alleviates salt-induced damage in safflower (Carthamus tinctorius L.) plants

Abstract: It has been shown that penconazole (PEN) acts as an endogenous signal molecule responsible for inducing stress tolerance in plants. The effect of PEN (15 mg l -1 ) and sodium chloride (0, 100, and 200 mM NaCl) on some biochemical and molecular responses of safflower was studied. Results revealed that chlorophylls and total soluble protein contents decreased under salinity, however total carotenoid, anthocyanin, flavonoid, and carbohydrate contents increased as well as SOS1 and NHX1 genes expression. The exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
2
1
0
Order By: Relevance
“…Exogenous PEN caused an increase in H 2 O 2 level. Our results are in agreement with findings in safflower plants [14] in which applied PEN had positive effects on plant growth under stress conditions. Plants respond to stress by increasing antioxidant capacity of cells to restore the cellular equilibrium [35].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Exogenous PEN caused an increase in H 2 O 2 level. Our results are in agreement with findings in safflower plants [14] in which applied PEN had positive effects on plant growth under stress conditions. Plants respond to stress by increasing antioxidant capacity of cells to restore the cellular equilibrium [35].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with other studies which reported promoting effect of triazoles on cytokinin content, cell division, and therefore growth enhancement in different plant species [29]. Accumulation of proline under stress conditions in many plant species has been correlated with stress tolerance [14,30]. Proline generally accumulates in response to environmental stresses in cytosol (Kishor et al 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation